Guin-Sapian a closer look at spiritual realm through a psychological lens; a case study of selected sapi victims in Leyte. - Gorgonia, Paul Anthony R., et al; Ilagan, Michael Joshua A.; Villero, Lowill John B. (Paul Anthony Gorgonia, Michael Joshua A. Ilagan, and Lowill John B. Villero, 2011)
The Sapi Phenomenon has long been engraved in the rich cultural heritage of the Philippines. Though there have been quite a handful of studies on this phenomenon, the researchers realized the need to take on a new study that would consider the multifaceted nature of sapi and the commonalities that occur among the victims. Therefore, this study was about the different elements and factors surrounding the phenomenon such as personal, social, spiritual factors, the symptoms, treatment, coping mechanisms, changes in the victim's lives, and the recommendations they gave. Placed alongside each other, these factors were analyzed and compared to identify the commonalities and parallel facets between and among the respondents. The following were the commonalities generated by the researchers from the ten sapi victims from Leyte who were subjected to a 77-item interview schedule. Results show that physical or psychological illness was absent in majority of the respondents. Sociability, good relationships with family and friends, and belief in God were not significant factors in predicting vulnerability to sapi. Nevertheless, majority of the respondents had encounters with supernatural entities which may have prompted a certain propensity to experience sapi. Majority of them admitted to engaging in occult activities either directly or indirectly which may have likewise prompted a certain predisposition to experience sapi. Majority of the reported symptoms were physical/somatic/motor in origin. Majority of the reported natural symptoms during sapi were behavioral in origin. Furthermore, majority of the respondents sought treatment from a tambalan or albularyo. All of the respondents employed spiritual coping. Majority became more sociable after the experience. All of the recommendations made by the ten respondents focused mainly on strengthening one's spirituality.